2018
DOI: 10.1016/j.matlet.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Micromorphology analysis of sputtered indium tin oxide fabricated with variable ambient combinations

Abstract: analysis of sputtered indium tin oxide fabricated with variable ambient combinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…For microelectronic applications, surfaces of Indium tin oxide (ITO) films should be atomically smooth to avoid electrical leakages; in fact, for such applications the interface width should be ~ 1 nm [4], [5]. Talu et al [6] reported that sputtered ITO films with higher root mean square roughness revealed higher sheet resistance and optical transmittance.…”
Section: Introduction mentioning
confidence: 99%
“…For microelectronic applications, surfaces of Indium tin oxide (ITO) films should be atomically smooth to avoid electrical leakages; in fact, for such applications the interface width should be ~ 1 nm [4], [5]. Talu et al [6] reported that sputtered ITO films with higher root mean square roughness revealed higher sheet resistance and optical transmittance.…”
Section: Introduction mentioning
confidence: 99%
“…Since the autocorrelation length ( S al ) does not directly convey information about the (an)isotropic properties of the surface, the texture aspect ratio ( S tr ) parameter was computed (Ţălu et al ., 2016a,b; Shapouri et al ., 2018) with the following relation (Nečas & Klapetek, 2012): Str=MaximumSalnormalMinimum0.28emSal.…”
Section: Methodsmentioning
confidence: 99%
“…While traditional analysis of SEM is based on visual or limited masked based analysis, there is a growing body of literature quantitatively exploring the data through machine vision (Yan et al ., 2019) and surface statistics (Ţălu et al ., 2016a,b; Klapetek, 2018). Roding et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations